SP Transcription Family Involve In Tooth Development ? - Ivan Arie Wahyudi (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2012)
Specificity Protein (SP) family members are tissue specific transcription factors.They regulate a wide range of cellular function including cells growth, apoptosis,differentiation and tumor formation. This family composed of more than 25member proteins, which contain a DNA-binding domain very well conservebetween all members with three tandem zinc fingers of the C2H2 type in theirCterminal region. Recently, it has reported in mammalian genome, there are nineSp genes (Sp1-Sp9). Some previous study reported Sp3 knockout mice haveenamel/dentin layer defect. Sp4 mRNA express in E13- E16 of WT mouse incisor.Sp7 mRNA express in at 15, 17 days of post coitum and P1 (postnatal day 1). Sp6has another name epiprofin, I also worked with this genes. Sp6 mRNA expressedin early stage of tooth development to the secretory stage of ameloblast. It alsoreported Sp6 weakly expressed in mesenchymal odontoblast of the incisor. Sp6deficient mice reported delay tooth development. SP family members play animportant role in tooth development.